Karl Rahner's Theological Project: A Response to R. R. Reno - Shields, Richard (Philosophy & theology, 2014)
This article responds to the article by R. R. Reno that appeared in the May 2013 issue of the journal First Things. In that article, Reno calls Rahner a restorationist, an integralist, and the “ultimate establishment theologian,” who reassured but failed to challenge the mind-set of the Church before Vatican II. Reno also claims that Rahner had a negative impact on the Church, blaming him for the many deficiencies Reno sees in contextual, feminist, liberation, and revisionist moral theology. The first part of this current article looks at the term intégrisme, and rebuts Reno’s suggestion that Rahner is an integralist. The second section explores Reno’s charge that “Rahner’s time has passed.” The third part examines the ecclesiologies of Reno and Rahner, highlighting the differences between the two and the implications for theology. The article concludes with a brief discussion of Rahner’s contribution to theology in his own right.